Semantic analysis of the Social Media discourse about the climate change: The focus of the public opinion on the Greta Thunberg, Australia fires and COP25 - Smolak Lozano, Emilia; Nakayama, Atsuho (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The study attempts to examine the complex universo of the global debate about environmental issues applying the models of linguistic analysis in order to extract semantic contents represented in the digital conversations of the Internet users. Computational linguistics allows recreating the semantic framework and contents of the online debate on the climate change applying the advances statistical models. Therefore, we have chosen the timeline of the digital discourse of Twitter users referring to climate change in the context of Australia fires, Greta Thunberg and COP25 summit.